A metal organic framework material and its preparation method and application
Cu-BDC-N2H3 metal organic framework material was prepared by ultrasonic reaction method, which solved the problems of high MOF synthesis temperature, long time and high detection limit, and achieved low detection limit and efficient adsorption effect on formaldehyde.
Patent Information
- Application Number
- CN202411401362.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing metal organic framework materials (MOFs) for formaldehyde adsorption have high synthesis temperature, long synthesis time and high detection limits, which limit their application in formaldehyde adsorption.
Cu-BDC-N2H3 is used as the metal organic framework material, which is prepared by ultrasonic reaction of 2-hydrazine-p-dibenzoic acid and copper salt in an organic solvent. This method reduces the synthesis temperature and time, improves the specific surface area of the material and selectivity for formaldehyde.
The low detection limit for formaldehyde is achieved, the synthesis conditions are mild, and the synthesis time is shortened, which significantly improves the synthesis efficiency and application potential of the material.
Smart Images

Figure CN119241859B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal organic framework materials, and in particular relates to a metal organic framework material and a preparation method and application thereof. Background Art
[0002] Aldehydes are a type of organic matter with active chemical properties that are prone to addition reactions and redox reactions, and only formaldehyde is in a gaseous state at room temperature and pressure. Formaldehyde is a colorless gas at low concentrations and is widely used in industries such as petrochemicals, biochemicals, medicine, textile engineering, and furniture decoration. Formaldehyde is also a toxic gas that seriously endangers human health. Poor-quality, substandard furniture and decoration materials easily volatilize high concentrations of formaldehyde. Long-term exposure to a high concentration of formaldehyde can cause tearing, headaches, and breathing difficulties. In severe cases, it can cause leukemia or even death. However, formaldehyde has a lighter odor at lower concentrations and is easily masked by other odors, which poses a challenge to the detection limit of formaldehyde detection reagents.
[0003] Metal organic framework (MOF) is a crystalline porous material formed by self-assembly of a central metal and an organic ligand interconnected by coordination bonds. It is a very promising gas adsorption material, not only because it has a large specific surface area, but also because it can graft functional groups that can chemically adsorb with target gas molecules onto organic ligand molecules to improve the selectivity of the material for target molecules. However, existing MOFs for formaldehyde adsorption generally face the disadvantages of too high synthesis temperature (100-150°C), too long synthesis time (12-36h), and high detection limit. These shortcomings limit the application of MOF in formaldehyde adsorption.
[0004] Therefore, there is an urgent need to provide a new material for adsorbing formaldehyde, which not only reduces the synthesis temperature and shortens the synthesis time, but also has a low detection limit for formaldehyde. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a metal organic framework material and a preparation method and application thereof. The metal organic framework material of the present invention has a low detection limit for formaldehyde, and the preparation method involves a low reaction or synthesis temperature and a short synthesis time, which significantly improves the synthesis efficiency of the metal organic framework material of the present invention and also reduces the synthesis cost.
[0006] A first aspect of the present invention provides a metal organic framework material.
[0007] Specifically, a metal organic framework material has a chemical formula of Cu-BDC-N2H3, wherein BDC represents terephthalic acid.
[0008] Preferably, the specific surface area of the metal organic framework material is 30-45 m2 ·g -1 , further preferably 33-38m 2 ·g -1 .
[0009] A second aspect of the present invention provides a method for preparing a metal organic framework material.
[0010] Specifically, a method for preparing a metal organic framework material comprises the following steps:
[0011] The metal organic framework material is prepared by mixing 2-hydrazino-p-dibenzoic acid, copper salt and an organic solvent and subjecting them to ultrasonic reaction.
[0012] Preferably, the mass ratio of the 2-hydrazino-p-dibenzoic acid to the copper salt is 0.01-0.5:(0.01-0.03), and more preferably 0.025-0.035:(0.01-0.015).
[0013] Preferably, the preparation method comprises the following steps:
[0014] Dissolving 2-hydrazino-p-dibenzoic acid in an organic solvent to obtain a 2-hydrazino-p-dibenzoic acid solution;
[0015] dissolving the copper salt to obtain a copper salt solution;
[0016] The copper salt solution is added into the 2-hydrazino-p-dibenzoic acid solution, and ultrasonic reaction is performed to obtain the metal organic framework material.
[0017] The structural formula of 2-hydrazino-p-dibenzoic acid is:
[0018] Preferably, the organic solvent comprises N,N-dimethylformamide (DMF).
[0019] Preferably, the mass volume ratio of the 2-hydrazino-p-dibenzoic acid solution to the organic solvent is (0.01-0.5) g:(10-15) mL, and more preferably (0.025-0.035) g:(11-12) mL.
[0020] Preferably, the copper salt comprises copper acetate or copper acetate monohydrate.
[0021] Preferably, when the copper salt is dissolved, the mass volume ratio of the copper salt to the solvent is (0.01-0.03) g:(2-8) mL, and more preferably (0.01-0.015) g:(3-5) mL.
[0022] Preferably, the ultrasonic reaction time is 2-20 minutes, further 10-20 minutes.
[0023] Preferably, the power of the ultrasonic reaction is 500-700W.
[0024] Preferably, the ultrasonic reaction is carried out at normal temperature and pressure, for example, at 10-40° C. under normal pressure without heating.
[0025] Preferably, the 2-hydrazino-p-dibenzoic acid is sonicated during the dissolution process, and the sonication time is 8-12 minutes.
[0026] Preferably, the copper salt is ultrasonicated during the dissolution process, and the ultrasonication time is 15-20 minutes.
[0027] Preferably, the copper salt solution is added to the 2-hydrazino-p-dibenzoic acid solution by dropwise addition for 2-5 minutes.
[0028] Preferably, after the ultrasonic reaction is completed, a suspension of the metal organic framework material is obtained, which is then centrifuged and washed.
[0029] Preferably, the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 5-10 minutes.
[0030] Preferably, the centrifugation and washing are performed 3-5 times.
[0031] Preferably, when washing is performed three times, the first washing is performed with methanol and the next two washings are performed with N,N-dimethylformamide.
[0032] The third aspect of the present invention provides the use of the above metal organic framework material in detecting formaldehyde.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0034] (1) The metal organic framework material of the present invention has a chemical formula of Cu-BDC-N2H3 and has a low detection limit for formaldehyde.
[0035] (2) The metal organic framework material of the present invention can be synthesized at room temperature and pressure. Compared with the traditional synthesis methods of most MOFs, the preparation method of the present invention has milder conditions and is easier to control. The synthesis time is greatly shortened to only a few minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 XRD pattern of Cu-BDC-N2H3 prepared in Example 1;
[0037] Figure 2 This is the SEM image of Cu-BDC-N2H3 prepared in Example 1;
[0038] Figure 3This is a graph showing the specific surface area test results of Cu-BDC-N2H3 prepared in Example 1;
[0039] Figure 4 The standard curve of Cu-BDC-N2H3 prepared in Example 1 for different concentrations of formaldehyde and fluorescence emission intensity;
[0040] Figure 5 This is a curve showing the change of fluorescence emission intensity versus reaction time when the Cu-BDC-N2H3 prepared in Example 1 adsorbs formaldehyde at a concentration of 100 ppb. DETAILED DESCRIPTION
[0041] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0042] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0043] Example 1: Preparation of metal organic framework materials
[0044] A metal organic framework material has a chemical formula of Cu-BDC-N2H3, wherein BDC represents terephthalic acid.
[0045] A method for preparing a metal organic framework material comprises the following steps:
[0046] 0.03 g of 2-hydrazino-p-dibenzoic acid was dissolved in 12 mL of organic solvent DMF and ultrasonicated for 10 minutes to obtain a 2-hydrazino-p-dibenzoic acid solution;
[0047] 0.015 g of copper acetate monohydrate was dissolved in 3 mL of DMF and ultrasonicated for 12 minutes to obtain a copper acetate solution;
[0048] The copper acetate solution was added dropwise to the 2-hydrazino-p-dibenzoic acid solution within 5 minutes, and the solution was subjected to ultrasonic reaction for 12 minutes. The solution was then centrifuged at a speed of 8000 rpm for 6 minutes. The solution was washed three times, the first time with methanol, and the next two times with N,N-dimethylformamide to obtain a metal organic framework material (Cu-BDC-N2H3).
[0049] Example 2: Preparation of metal organic framework materials
[0050] A method for preparing a metal organic framework material comprises the following steps:
[0051] Dissolve 0.025 g of 2-hydrazino-p-dibenzoic acid in 10 mL of organic solvent DMF and perform ultrasonication for 10 minutes to obtain a 2-hydrazino-p-dibenzoic acid solution;
[0052] Dissolve 0.01 g of copper acetate in 4 mL of DMF and sonicate for 12 minutes to obtain a copper acetate solution;
[0053] The copper acetate solution was added dropwise to the 2-hydrazino-p-dibenzoic acid solution within 5 minutes, and the solution was subjected to ultrasonic reaction for 10 minutes. The solution was then centrifuged at a speed of 8000 rpm for 6 minutes. The solution was washed three times, the first time with methanol, and the next two times with N,N-dimethylformamide to obtain a metal organic framework material (Cu-BDC-N2H3).
[0054] Example 3
[0055] Compared with Example 1, the difference of Example 3 is that the copper acetate monohydrate in Example 1 is replaced by an equal amount of copper nitrate pentahydrate, and the rest of the process is the same as that of Example 1.
[0056] Comparative Example 1
[0057] The only difference from Example 1 is that in Comparative Example 1, the 2-hydrazino-p-dibenzoic acid solution and the copper acetate solution are mixed, placed in a high-pressure reactor, and heated at 130° C. for 6 hours. The other processes are the same as in Example 1 (i.e., the reaction conditions are changed in Comparative Example 1 relative to Example 1).
[0058] Comparative Example 2
[0059] The only difference from Comparative Example 1 is that Comparative Example 2 is heated and reacted at 130° C. for 12 hours, and the other processes are the same as Comparative Example 1 (that is, Comparative Example 2 has a longer heating reaction time than Comparative Example 1).
[0060] Comparative Example 3
[0061] The only difference from Comparative Example 1 is that in Comparative Example 3, all DMF is replaced with an equal volume of water, and the other processes are the same as those in Comparative Example 1 (i.e., the type of solvent is changed in Comparative Example 3 relative to Comparative Example 1).
[0062] Comparative Example 4
[0063] The only difference from Comparative Example 1 is that the centrifugal speed in Comparative Example 4 is set to 3000 rpm, and the other processes are the same as those in Comparative Example 1 (ie, the centrifugal speed in Comparative Example 4 is lower than that in Comparative Example 1).
[0064] Product effect testing
[0065] 1. Metal-organic framework material structure and adsorption performance test
[0066] Figure 1 XRD pattern of Cu-BDC-N2H3 prepared in Example 1; Figure 1 (“Intensity” means intensity, and “2θ (deg)” means diffraction angle (degree)) It can be seen that the metal organic framework material prepared in Example 1 has a chemical formula of Cu-BDC-N2H3.
[0067] Figure 2 The SEM image of Cu-BDC-N2H3 prepared in Example 1; Figure 2 It can be seen that the microstructure of Cu-BDC-N2H3 is a two-dimensional nanosheet with a high specific surface area, which provides more active sites for it to adsorb formaldehyde molecules.
[0068] Figure 3 The specific surface area test result diagram of Cu-BDC-N2H3 prepared in Example 1; Figure 3 ( Figure 3 V a Va represents the pore volume of 1 gram of Cu-BDC-N2H3 under standard conditions, p represents the gas phase pressure at adsorption equilibrium, p0 represents the saturated vapor pressure of the gas at the adsorption temperature, p / p0 represents the relative pressure, "Adsorption" represents adsorption, and "Desorption" represents desorption). The specific surface area of Cu-BDC-N2H3 is 33.8444m 2 ·g -1 .
[0069] Figure 4 The standard curve of Cu-BDC-N2H3 prepared in Example 1 for different concentrations of formaldehyde and fluorescence emission intensity; Figure 4 The horizontal axis “Concentration FA ” represents the formaldehyde concentration, and the vertical axis “Sensitivity” represents the change rate (also called sensitivity) of the fluorescence emission intensity of different concentrations of formaldehyde compared with the blank control group (the formaldehyde concentration of the blank control group is 0 and the volume proportion of nitrogen is 100%). The fitting equation is the Langmuir equation, R 2 It represents the correlation coefficient, from which it can be seen that the detection limit of formaldehyde adsorption by Cu-BDC-N2H3 prepared in Example 1 is as low as 25ppb.
[0070] Figure 4 The equation of the standard curve in is: Wherein, x is the formaldehyde concentration (ppb), y is the sensitivity (Sensitivity), and the sensitivity calculation process is: y = (I1-I0) / I0×100%, wherein I1 is the fluorescence emission intensity measured by Cu-BDC-N2H3 adsorbing a certain concentration of formaldehyde, and I0 is the fluorescence emission intensity of the Cu-BDC-N2H3 test blank group, and its value is 15227.69.
[0071] Figure 5 The curve of fluorescence emission intensity versus reaction time when Cu-BDC-N2H3 prepared in Example 1 adsorbs 100 ppb formaldehyde. The horizontal axis "Time" is the reaction time of Cu-BDC-N2H3 and formaldehyde, and the vertical axis "Intensity" is the fluorescence emission intensity. When the reaction time reaches more than 36 hours, the fluorescence emission intensity is the maximum.
[0072] 2. Formaldehyde detection accuracy
[0073] The metal organic framework materials prepared in the above examples and comparative examples were used to detect formaldehyde according to the following steps:
[0074] The metal organic framework material is dispersed in 90mL of DMF, stirred until uniformly dispersed, and a dispersion is obtained. 8mL of the dispersion is placed in a sample bottle, and 200mL of formaldehyde (the concentration of formaldehyde is 100ppb, diluted from 10ppm formaldehyde, diluted with nitrogen, and purchased from Dalian Data Gas Co., Ltd., with a factory date of June 5, 2024) is injected into the sample bottle (the sample bottle volume is 10mL) using a syringe pump. After standing for 2 days, the fluorescence emission intensity of the sample (metal organic framework material after adsorption of formaldehyde) is tested at an excitation wavelength of 360nm. The fluorescence emission intensity corresponding to the metal organic framework material prepared in the above embodiment and comparative example and the accuracy of detecting formaldehyde are obtained, and the results are shown in Table 1.
[0075]
[0076] Table 1 shows the theoretical value of the fluorescence emission intensity corresponding to 100 ppb formaldehyde, which is calculated by substituting 100 ppb into the above standard curve equation.
[0077] The calculation process of the accuracy of formaldehyde is: accuracy = (I3-I2) / I2×100%; wherein I3 is the fluorescence emission intensity corresponding to each embodiment and comparative example, and I2 is the theoretical value 20467.23 in Table 1.
[0078] As can be seen from Table 1, compared with Example 1, Example 3 has four more crystal waters than the copper acetate monohydrate used in Example 1 because the copper nitrate pentahydrate used in Example 3 has four more crystal waters than the copper acetate monohydrate used in Example 1. The crystal water is soluble in DMF, which will dilute the alkalinity of Cu-BDC-N2H3 itself and inhibit the fluorescence emission intensity of the acetal reaction between the hydrazine group and the aldehyde group.
[0079] It can be seen from Example 1 and Comparative Example 1 that although the performance of the metal organic framework material prepared under high temperature and high pressure conditions in Comparative Example 1 in detecting formaldehyde is comparable to that in Example 1, the reaction conditions in Comparative Example 1 are obviously harsh, the production cost is high, and the preparation time is long, resulting in low production efficiency.
[0080] It can be seen from Comparative Examples 1 and 2 that copper acetate and 2-hydrazino-p-dibenzoic acid can rapidly undergo coordination reaction at room temperature to generate Cu-BDC-N2H3 with a certain crystallinity, and the yield that can be improved by increasing the temperature is limited.
[0081] It can be seen from Comparative Examples 1 and 3 that 2-hydrazino-p-dibenzoic acid has a low solubility in water and is difficult to react with copper acetate in an aqueous medium. The yield of the metal organic framework material is low, so the fluorescence emission intensity after the reaction with formaldehyde is low.
[0082] It can be seen from Comparative Examples 1 and 4 that the faster the centrifugal speed, the easier it is for the Cu-BDC-N2H3 suspended in DMF to settle and be collected. When the speed is reduced, only part of the Cu-BDC-N2H3 can be deposited, and the rest is still dispersed in DMF, resulting in a lower yield, so the fluorescence emission intensity after reacting with formaldehyde is smaller.
Claims
1. A metal organic framework material, characterized in that: Its chemical formula is Cu-BDC-N2H3, where BDC represents terephthalic acid; The method for preparing the metal organic framework material comprises the following steps: Mixing 2-hydrazino-terephthalic acid, copper salt and organic solvent, and subjecting to ultrasonic reaction to obtain the metal organic framework material; The organic solvent is N,N-dimethylformamide; The mass ratio of the 2-hydrazino-terephthalic acid to the copper salt is 0.01-0.5:(0.01-0.03); After the ultrasonic reaction is completed, a suspension of the metal organic framework material is obtained, which is then centrifuged and washed; The centrifugal speed is 8000-10000rpm, and the centrifugal time is 5-10 minutes; The mass volume ratio of the 2-hydrazino-terephthalic acid to the organic solvent is (0.01-0.5) g: (10-15) mL; The mass volume ratio of the copper salt to the organic solvent is (0.01-0.03) g: (2-8) mL; The ultrasonic reaction time is 2-20 minutes; The ultrasonic reaction is carried out at normal temperature and pressure.
2. The metal organic framework material according to claim 1, characterized in that The specific surface area of the metal organic framework material is 30-45 m 2 ·g -1 .
3. The method for preparing the metal organic framework material according to claim 1 or 2, characterized in that: The following steps are involved: Mixing 2-hydrazino-terephthalic acid, copper salt and organic solvent, and subjecting to ultrasonic reaction to obtain the metal organic framework material; The organic solvent is N,N-dimethylformamide; The mass ratio of the 2-hydrazino-terephthalic acid to the copper salt is 0.01-0.5:(0.01-0.03); After the ultrasonic reaction is completed, a suspension of the metal organic framework material is obtained, which is then centrifuged and washed; The centrifugal speed is 8000-10000 rpm, and the centrifugal time is 5-10 minutes.
4. The preparation method according to claim 3, characterized in that: The following steps are involved: Dissolving 2-hydrazino-terephthalic acid in an organic solvent to obtain a 2-hydrazino-terephthalic acid solution; dissolving the copper salt to obtain a copper salt solution; The copper salt solution is added to the 2-hydrazino-terephthalic acid solution for ultrasonic reaction. After the ultrasonic reaction is completed, a suspension of a metal organic framework material is obtained, which is then centrifuged and washed to obtain the metal organic framework material.
5. The preparation method according to claim 3, characterized in that: The copper salt includes copper acetate or copper acetate monohydrate.
6. Use of the metal organic framework material according to claim 1 or 2 in detecting formaldehyde.
Citation Information
Patent Citations
Metal-organic framework material, preparation method thereof and immunosensor
CN111234243A
Metal organic framework material containing Schiff base ligand, catalyst, preparation and application
CN112390959A